2016
DOI: 10.1096/fj.201600321r
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial BMI1 maintains bioenergetic homeostasis in cells

Abstract: The polycomb complex proto-oncogene BMI1 [B lymphoma Mo-MLV insertion region 1 homolog (mouse)] is essential for self-renewal of normal and cancer stem cells. BMI1-null mice show severe defects in growth, development, and survival. Although BMI1 is known to exert its effect in the nucleus via repression of 2 potent cell-cycle regulators that are encoded by the Ink4a/Arf locus, deletion of this locus only partially rescues BMI1-null phenotypes, which is indicative of alternate mechanisms of action of BMI1. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 81 publications
3
12
1
Order By: Relevance
“…Polycomb-related BMI1 protein is necessary for the maintenance of several adult stem cell populations, mainly through its capacity to inhibit senescence-related genes and to regulate mitochondrial function. 48, 49 In-depth analysis of how BMI1 acts has nonetheless allowed description of specific tissue-related functions. In mesenchymal cells, BMI1 inhibits the expression of key chemokines from the senescence-associated secretory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Polycomb-related BMI1 protein is necessary for the maintenance of several adult stem cell populations, mainly through its capacity to inhibit senescence-related genes and to regulate mitochondrial function. 48, 49 In-depth analysis of how BMI1 acts has nonetheless allowed description of specific tissue-related functions. In mesenchymal cells, BMI1 inhibits the expression of key chemokines from the senescence-associated secretory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been illustrated that cells lacking BMI1 exhibit mitochondrial dysfunction, the disturbance of reactive oxygen species (ROS) homeostasis, and the activation of DNA damage response (DDR) pathway; correspondingly, antioxidants or interruption of DDR pathway can rescue the deficiency of BMI1 [35] . BMI1 was also found present in the inner mitochondrial membrane, beyond its previously described nuclear localization, and participated in the direct modulation of mitochondrial bioenergetics; meanwhile, BMI1 deficiency resulted in reduced stability of mitochondrial RNA and increased ribonuclease activity of polynucleotide phosphorylase [36] . With regard to the cardiovascular field, Herrero and colleagues provided evidence on the contribution of BMI1 in the turnover of adult progenitor cells in response to cardiac oxidative stress [37] : in the cardiac steady-state, BMI1 mainly binds to the canonical cell fate-related DNA targets in cardiac progenitors; while in response to an accumulation of ROS triggered by oxidative stress, BMI1 delocalized from DNA canonical targets to the non-canonical ones and regulated the terminal differentiation of cardiac stem cells to CMs, and it has been observed that 25% of the CM-committed cells in adult mice are derived from BMI1 + cardiac cells.…”
Section: Novel Roles Of Bmi1 In the Heartmentioning
confidence: 86%
“…Bmi1 is important for the self-renewal of stem cells. Bmi1 modulates mitochondrial function (41), ROS generation, and DNA double-strand break repair (42), and regulates the function and apoptosis of various types of cells, such as stem cells and cancer cells (43,44). Therefore, the present study examined whether Shh pathway activation regulates Bmi1 in diabetic EPCs.…”
Section: Discussionmentioning
confidence: 99%